An Existence Theorem for Fractional q-Difference Inclusions with Nonlocal Substrip Type Boundary Conditions - Ahmed Alsaedi; Sotiris K. Ntouyas; Bashir Ahmad (The Scientific World Journal)
By employing a nonlinear alternative for contractive maps, we investigate the existence of solutions for a boundary value problem of fractional q-difference inclusions with nonlocal substrip type boundary conditions. The main result is illustrated with the aid of an example.